IMPLEMENTASI ETOS KERJA ISLAMI DALAM MENINGKATKAN KINERJA KARYAWAN SEMENTARA BANK SYARIAH INDONESIA TBK CABANG KETAPANG - Alif Akbarul Muslim (Al-Idarah, 2023)
One of the obligations of every Muslim is to work (earn a living). Because by working a Muslim can realize himself in meeting his needs in the world, because earning a living in a good way is included in the group of people who are jihad fisabilillah. Meanwhile, Bank Syariah Indonesia Tbk Ketapang Branch is a facilitator of sharia-based economic activities. One important aspect of the Islamic economy is economic actors, both owners of capital and employees. Therefore the character of workers is very influential in improving the economy. Based on this, researchers are interested in discussing the application of the Islamic work ethic in improving employee performance. This research focuses on the issues of (1.) how to implement the Islamic work ethic in improving employee performance at Bank Syariah Indonesia Tbk Ketapang Branch, West Kalimantan Province (2.) what are the supporting and inhibiting factors for implementing Islamic work ethic in improving employee performance at Bank Syariah Indonesia Tbk Ketapang Branch West Kalimantan Province. This research uses descriptive qualitative research, which is a research procedure that aims to make a systematic, actual and accurate explanation of the facts that happened at Bank Syari'ah Indonesia Tbk, Ketapang Branch. The results of this study indicate that the implementation of the Islamic work ethic at Bank Syariah Indonesia (BSI) Tbk Ketapang Branch is in accordance with the principles and characteristics of the existing Islamic work ethic, namely: having clean morality (sincere), having honesty, and having a responsible soul. answer. .